Comprehensive Midwifery Care For Mrs. “Y” G3P2A0 Through The Use Of Perineal Massage Video To Prevent Perineal Laceration At Melong Asih Community Health Center - Nabilah, Naifah; Putriastuti, Widya; Fatonah, Sofa; Maryati, Sri (Indonesian Health Journal, 2025)
Vaginal delivery is often accompanied by anatomical changes in the perineum, one of which is perineal laceration, experienced by approximately 85% of women who give birth spontaneously. This laceration can affect the mother's recovery and quality of life during the postpartum period. Perineal massage can help prevent tears by increasing the elasticity of perineal tissue, preparing it for stretching during childbirth, and reducing the risk of tears. This study aims to provide comprehensive care using perineal massage techniques from pregnancy to prevent perineal lacerations. The method used is descriptive with a case study approach, data collection through interviews and physical examinations. The study subject was Mrs. "Y" G3P2A0, who received perineal massage from 36 weeks of pregnancy until childbirth. The results showed that perineal elasticity improved from the rigid category to the elastic category after regular perineal massage for 4 weeks prior to childbirth, with a frequency of 5 times per week. During childbirth, a contraction timer was used to monitor progress. During the postpartum period, mothers complained of sore nipples and were given breastfeeding techniques. Perineal massage had a significant effect in preventing perineal lacerations with a frequency of 5 times a week for 4 weeks before delivery. Perineal massage increased tissue elasticity, improved blood circulation, and trained relaxation during labor. Success is supported by the mother's compliance and proper massage technique. This care is expected to be applied to pregnant women up to the postpartum period.